Advanced welding and deforming - Davim, J. Paulo; Gupta, Kapil (Elsevier, 2021)
Advanced Welding and Deforming explains the background theory, working principles, technical specifications, and latest developments on a wide range of advanced welding-joining and deforming techniques. The book's subject matter covers manufacturing, with chapters specifically addressing remanufacturing and 3D printing applications. Drawing on experts in both academia and industry, coverage addresses theoretical developments as well as practical improvements from R&D. By presenting over 35 important processes, from plasma arc welding to nano-joining and hybrid friction stir welding, this is the most complete guide to this field available. This unique guide will allow readers to compare the characteristics of different processes, understand how they work, and create parameters for their effective implementation. As part of a 4 volume set entitled Handbooks in Advanced Manufacturing, this series also includes volumes on Advanced Machining and Finishing, Additive Manufacturing and Surface Treatment, and Sustainable Manufacturing Processes.- Resumé vydavatel
Keywords: svařování; deformace; welding; deformations (mechanics); elektronické knihy; příručky; electronic books; handbooks and manuals